Balance-Sheet Shocks and Recapitalizations - Sandri, Damiano; Valencia, Fabian (Washington, D.C. : International Monetary Fund, 2012)
We develop a dynamic stochastic general equilibrium model with financial frictions on both financial intermediaries and goods-producing firms. In this context, due to high leverage of financial intermediaries, balance sheet disruptions in the financial sector are particularly detrimental for aggregate output. We show that the welfare gains from recapitalizing the financial sector in response to large but rare net worth losses are as large as those from eliminating business cycle fluctuations. We also find that these gains are increasing in the size of the net worth loss, are larger when recapitalization funds are raised from the household rather than the real sector, and may increase with a reduction in financial intermediaries idiosyncratic risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States